Reseña a: Löic Menanteau (dir.), Sels et salines de l’Europe atlantique, Presses Universitaires, Rennes 2018 (503 p.) - Martín Gutiérrez, Emilio (Riparia, 2019)
Reseña a: Löic Menanteau (dir.), Sels et salines de l’Europe atlantique, Presses Universitaires, Rennes 2018 (503 p.)